Implementasi Hak Pendidikan dan Pengajaran Anak Binaan di Lembaga Pembinaan Khusus Anak Kelas II Kendari dalam Tinjauan Maslahah - Elminary Arnaj; Ahmad Ahmad (QAIMUDDIN: Journal of Constitutional Law Review, 2021)
This study aims to determine the implementation of Law No. 12 of 1995 concerning correctional facilities and the views of Al-maslahah ad-dharuriyyah on the Implementation of the Right to Education and Teaching of Children in the Special Guidance for Class II Kendari Children in the Maslahah Review. The results of the study show that the implementation of Law Number 12 of 1995 concerning Corrections has been carried out but has not run optimally because there is no level of education. Al-Maslahah Ad-Dharuriyyah's View on the Implementation of Law Number 12 of 1995 Education and teaching at a special coaching institution for class II Kendari children will run well if the implementation of Law Number 12 of 1995 concerning Corrections runs optimally. After doing research.